2014
DOI: 10.1155/2014/526391
|View full text |Cite|
|
Sign up to set email alerts
|

Mannosylated Chitosan Nanoparticles for Delivery of Antisense Oligonucleotides for Macrophage Targeting

Abstract: The therapeutic potential of antisense oligonucleotides (ASODN) is primarily dependent upon its safe and efficient delivery to specific cells overcoming degradation and maximizing cellular uptake in vivo. The present study focuses on designing mannosylated low molecular weight (LMW) chitosan nanoconstructs for safe ODNs delivery by macrophage targeting. Mannose groups were coupled with LMW chitosan and characterized spectroscopically. Mannosylated chitosan ODN nanoparticles (MCHODN NPs) were formulated by self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 131 publications
(147 reference statements)
2
32
0
Order By: Relevance
“…RAW 264.7 macrophages for other HA-based nanomaterials, such as HA-coated liposomes [36] and a library of lipid nanoparticles with surface-anchored HA [37], or chitosan-based carriers, such as mannosylated chitosan nanoparticles [38] or siRNA-entrapped chitosan nanoparticles (with or without TPP) [39]. The innocuous character of HA-coated chitosan nanoparticles in HCT-116 is also consistent with previous studies on HA-based cationic nanocarriers [40,41].…”
Section: Evaluation Of Cd44-targeted Delivery Of Sirnasupporting
confidence: 85%
“…RAW 264.7 macrophages for other HA-based nanomaterials, such as HA-coated liposomes [36] and a library of lipid nanoparticles with surface-anchored HA [37], or chitosan-based carriers, such as mannosylated chitosan nanoparticles [38] or siRNA-entrapped chitosan nanoparticles (with or without TPP) [39]. The innocuous character of HA-coated chitosan nanoparticles in HCT-116 is also consistent with previous studies on HA-based cationic nanocarriers [40,41].…”
Section: Evaluation Of Cd44-targeted Delivery Of Sirnasupporting
confidence: 85%
“…Observations have confirmed that the ability to bind specifically to macrophages and transfection efficiency of mannosylated CS nanoparticles containing gastrin‐releasing (pGRP) peptide were significantly higher than those of uncoated particles as macrophages (such as Kupffer cells) express a range of mannose specific membrane receptors which uptake glycoproteins bearing high mannose chains by clathrin‐coated vesicles for delivery into the endosomal system . Furthermore, mannosylated CS nanoparticles exhibited a much higher transfection efficiency into Raw 264.7 cells (bears mannose receptors) than HeLa cells and successfully found as an ideal targeting gene delivery vehicle to the macrophages . Oleoyl CS nanoparticles have been employed as another promising system for the delivery of hydrophobic antitumour agents.…”
Section: Polysaccharide Nanoparticlesmentioning
confidence: 86%
“…CS has been extensively studied as a vehicle for gene transfer into a wide range of cells because of its high efficiency to condense DNA and siRNA . Positively charged CS can compact negatively charged nucleic acids in the form of nanoscale complexes, resulting in protection of the nucleic acids from degradation and improved cellular uptake as compared to the naked nucleic acids .…”
Section: Polysaccharide Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…These treatment regimes are primarily based on the patternrecognition receptors which are present on the cell surface of macrophages such as the family of scavenger receptors, examples include Fc and complement receptors, mannose receptor Fig. 5 [175][176][177][178][179][180], which are used by macrophages for phagocytosis [181][182][183][184]. In many cases, receptors for amyloid-b peptide [185], high-density lipoprotein [186] and hyaluronic acid [187] were utilized as a candidate for targeted delivery of drug.…”
Section: Nanoparticle Targeting With Macrophages To Control Inflammationmentioning
confidence: 99%